Joined-up Governance of Agri-Food Systems in Canada: An Examination of Food Policy Councils as a Form of Joined-up Governance - La Forge, Sylvie (Université d'Ottawa | University of Ottawa, 2019)
Agri-food policy has traditionally been addressed by different governmental agencies and jurisdictions. Departments of Agriculture and Health as well as provincial and municipal governments shape the different aspects of agri-food systems, generating disjointed policies (Barling et al., 2002). Food policy councils (FPCs) at the local and regional levels have emerged across North America, both in response to this fragmented approach and to the detrimental effects of the dominant agri-food system. One of the main objectives of these councils is to bring diverse stakeholders together to address the multiple and related challenges within agri-food systems including food access, environmental sustainability, and health (Borron, 2003). Within this context, this explorative research examines how and in which ways existing FPCs can contribute to a national food policy framework in Canada. Drawing on literature from public management, this paper demonstrates in what ways FPCs contribute—or have the potential to contribute—to a joined-up governance of agri-food policy in Canada. It also highlights what FPCs can learn from existing studies and experiences of joined-up governance initiatives in other sectors as a way to increase their effectiveness.